Nurturing individual job performance through psychological capital power - Andri, Gus; Rabiatul Adawiyah, Wiwiek; Purnomo, Ratno; Candra, Yuni (BISMA (Bisnis dan Manajemen), 2021)
The overarching objectives of this inquiry are twofold: first, to investigate the relationship between proactive personality, empowering leadership, and individual job performance; second, to examine the mediating role of psychological capital on the relationship between empowering leadership and an individual’s job performance. The sample consists of 215 entrepreneurs of Minang migrants in Purwokerto-Central Java, Indonesia. The Minangnese is an ethnic group in Indonesia with a high success rate of entrepreneurs, and hence there is a stigma in the society that the Minang tribe was born to be entrepreneurs. Despite the abundant literature on entrepreneurship, few have focused on the leadership style of specific ethnicities in doing business. The burgeoning popularity of entrepreneurship theory has attracted academic attention. Scholars attempt to enhance the entrepreneurship literature from various perspectives, one of which is a cultural value. Moreover, little discussion on the role of psychological capital in nurturing individual job performance is the primary motive behind the study. Data were collected using a questionnaire and analysis with Structural Equation Modeling (SEM). The results proactive personality positively influences empowering leadership. Likewise, empowering leadership determines both psychological capital and individual job performance. The study also supported the view that psychological capital mediates the relationship between empowering leadership and individual performance. The theoretical implication of this research is that psychological capital is important in building individual characters who respond to difficult conditions, so that psychological capital is a competency in improving individual performance.